2002
DOI: 10.1093/bja/88.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, placebo-controlled analgesic study of ibuprofen or rofecoxib in combination with paracetamol for tonsillectomy in children

Abstract: This study provides evidence to support the combination of ibuprofen (but not rofecoxib) with paracetamol for perioperative analgesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
1
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 27 publications
8
131
1
13
Order By: Relevance
“…14 Results of all three studies showed the combination treatment to be superior to acetaminophen alone, although studies comparing the combination treatment with ibuprofen alone showed conflicting results. 14,16 These conclusions are inconsistent with our data showing no difference between the three treatments with regard to the primary outcome measure. Our secondary findings are more aligned with this previous work.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…14 Results of all three studies showed the combination treatment to be superior to acetaminophen alone, although studies comparing the combination treatment with ibuprofen alone showed conflicting results. 14,16 These conclusions are inconsistent with our data showing no difference between the three treatments with regard to the primary outcome measure. Our secondary findings are more aligned with this previous work.…”
Section: Discussioncontrasting
confidence: 79%
“…8 Data pertaining to children are limited to three studies using a variety of pain assessment techniques and outcome measures in tonsillectomy and dental pain models. [14][15][16] All of these studies assessed the combination of acetaminophen and ibuprofen using a single-dose design, and one used a rectal route of administration. 14 Results of all three studies showed the combination treatment to be superior to acetaminophen alone, although studies comparing the combination treatment with ibuprofen alone showed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Combining nsNSAIDs and paracetamol has been shown to improve analgesia and/or decrease the need for additional analgesia after adenoidectomy (Viitanen et al, 2003 Level II), tonsillectomy (Pickering et al, 2002 Level II), inguinal surgery (Riad & Moussa, 2007 Level II), multiple dental extractions (Gazal & Mackie, 2007 Level II), and orthopaedic surgery (Hiller et al, 2006 Level II). As a component of multimodal analgesia, nsNSAIDs decrease opioid consumption (Antila et al, 2006 Level II; Rugyte & Kokki, 2007 Level II).…”
Section: Non-selective Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…In a recent study in children undergoing appendicectomy, paracetamol with diclofenac did not provide additional benefit compared with either drug alone. In contrast, the addition of ibuprofen to paracetamol reduced the need for early analgesia from 72 to 38% after tonsillectomy in children 3-15 years [10]. No previous studies have addressed postoperative pain relief after inguinal hernia surgery using pre-operative administration of paracetamol and diclofenac.…”
mentioning
confidence: 99%